2022
DOI: 10.1177/09544089221074837
|View full text |Cite
|
Sign up to set email alerts
|

A RSM based MOGOA for process optimization during WEDM of Inconel 625

Abstract: Inconel 625 is a super alloy that has excellent thermal and mechanical properties but is arduous to machine with conventional machining processes due to high melting point and hardness. Wire Electro Discharge machining, that have been an avowed unconventional process of machining that is mainly applied for the machining of tough and hard materials such as Inconel 625. An attempt, in this article, have been made to optimize the WEDM process parameters like servo voltage, peak current, spark-on time, spark-off t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Step 5: The optimal outcomes produced by the ANN-VCPSO are compared with optimum data generated by the RSM-desirability. [24][25][26] Step 6: Evaluation of the total honing cost at the optimal solution. The total honing cost (THC) comprises the labor (LAC), machine (MC), energy (EEC), honing tool (HTC), lubricant (LC), maintenance (MAC), cleaning (CLC), and disposal (CD) costs.…”
Section: Optimization Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 5: The optimal outcomes produced by the ANN-VCPSO are compared with optimum data generated by the RSM-desirability. [24][25][26] Step 6: Evaluation of the total honing cost at the optimal solution. The total honing cost (THC) comprises the labor (LAC), machine (MC), energy (EEC), honing tool (HTC), lubricant (LC), maintenance (MAC), cleaning (CLC), and disposal (CD) costs.…”
Section: Optimization Approachmentioning
confidence: 99%
“…Step 5: The optimal outcomes produced by the ANN-VCPSO are compared with optimum data generated by the RSM-desirability. 2426…”
Section: Optimization Approachmentioning
confidence: 99%
“…Here, the modeling method was based on Taguchi L 16 and RSM. The desired setting was obtained using a Multi-Objective Grasshopper optimization algorithm (MOGOA) [49]. In the same year, N. Kumar et al represented a review article about various parameters of WEDM using different optimization methods and concluded that MRR and SR are the most repeated output parameters [50].…”
Section: Introductionmentioning
confidence: 99%